Study On The Creative Process Of VJ-Ing In Kuala Lumpur - Mat Yusoff, Nur Huda (2011)
In this paper, the objective is to investigate VJs creative work processes from the pre-production, production to the actual live performance. The processes will be by investigating the step by step process starting from beginning to the day of the performance.